Which one will you choose; open, laparoscopic, or robotic transduodenal ampullectomy?: a case report - Dawn Jung; Ji Eun Jung; Chang Moo Kang (Journal of Minimally Invasive Surgery)
Transduodenal ampullectomy (TDA) is the treatment of choice for large premalignant lesions of the ampulla of Vater (AoV). With the development of surgical techniques, various methods, including the open, laparoscopic, and robotic approaches, for performing TDA have emerged. Herein, we report four consecutive cases treated with open, laparoscopic, and robotic TDA, with technical pitfalls and future perspectives of TDA in treating premalignant lesions of the AoV. The surgical techniques and principles for TDA were the same regardless of the surgical approaches. After surgery, none of the patients showed any abnormal findings or complications, except for digestive problems. All these surgical approaches are appropriate for patients requiring TDA; however, minimally invasive TDA, particularly the robotic approach is ideal. Considering the surgical complexity of TDA, the robotic approach is considered to be effective.